Simultaneous Oculomotor and Facial Nerve Palsies in a Patient with Systemic Lupus Erythematosus and Sjögren's Syndrome. (11th April 2019) - Shima, Natsuki; Murosaki, Takamasa; Yamamoto, Shotaro; Miyanaga, Akiko; Kusaka, Hiroi; Nagatani, Katsuya; Nagashima, Takao; Sawada, Mikio; Iwamoto, Masahiro; Minota, Seiji
Abstract : A 70-year-old man with systemic lupus erythematosus (SLE) presented with simultaneous right oculomotor nerve palsy and right facial nerve palsy. Brain magnetic resonance imaging and cerebrospinal fluid analysis revealed no abnormality. Coexistent Sjögren's syndrome was diagnosed on the basis of anti-SS-A antibody positivity, salivary gland scintigraphy, and histological findings on minor salivary gland biopsy. As there was no obvious cause of multiple cranial neuropathies, we supposed that the palsies were induced by either of the underlying diseases. The patient was treated with a high-dose of prednisolone and intravenous cyclophosphamide, and both palsies recovered almost completely within two weeks.